Hypogonadism in males exposed to mixed chemicals in a mechanic village in Bodija, Ibadan (2015)
Africa has great intensity of chemical exposure and high level of infertility. Functional disorders of the male germ cell and endocrinopathies have been attributed to exposure to mixed chemicals. Data on the mixed chemical exposure on reproductive hormones are sparse in Nigeria. This study was designed to evaluate male reproductive hormones and determinants of occupational exposure to mixed chemicals in a mechanic village in Ibadan. Forty-three males, auto mechanics aged 18-60 years occupationally exposed to mixed chemicals (MCG) at their work place in Bodija mechanic village with mean±SEM duration of 21.2±1.9 years were age matched with 40 unexposed males (controls) from the University College Hospital, Ibadan and environs. Demography, anthropometry, blood pressure and sexual history were obtained by standard methods. Blood (10 ml) was obtained from each participant for estimation of reproductive hormones by enzyme linked immunosorbent assay while total antioxidant capacity (TAC) was determined spectrophotometrically. Testosterone/oestradiol ratio (TE ratio) was calculated. The MCG were classified based on their reproductive hormone levels into 4 subgroups as eugonadic, hypogonadotrophic hypogonadism, sub-optimal hypogonadism and compensated hypogonadism. P<0.05 was regarded as significant. There were significantly raised oestradiol levels, diastolic blood pressure, waist circumference and waist to hip ratio and significantly lower TAC and TE ratio in the MCG than the controls (P<0.01). Exposed hypogonadic males exhibited significantly lower LH, FSH, testosterone, prolactin, TAC levels and TE ratio than exposed eugonadic males (P<0.05). Hypogonadism in the males exposed to mixed chemicals may be associated with reduced TE ratio resulting from increased adipose mass as well as oxidative stress associated with the mixed chemical exposure.